Are you readieee? Taking the "eek" out of participating in fully online communities: Exploring Readiness using the Fully Online Learning Community (FOLC) Model - Childs, Elizabeth; van Oostveen, Roland (Proceedings of the International Conference on Networked Learning, 2018)
This workshop will provide an overview of the theoretical underpinnings and description of the FOLC model and its component parts. Through small group activities, participants will examine and discuss propositional definitions for the FOLC components. Participants will complete the FOLCS online self-assessment instrument and discuss their experience with a focus on improving the FOLCS for global use. In addition, participants will examine the application of the FOLCS for use with their students as a component of determining readiness to moving into fully online learning environments. The workshop will conclude with an explanation of the global educational learning observatory (GELO) and its associated tool set will be shared and participants will be invited to join into this global research network.